Battlestar Galactica and international relations - Neumann, Iver B.; Kiersey, Nicholas J. (New York : Routledge, 2013)
"Tackling some of the key contemporary issues in IR, the writers of BSG have taken on a range of important political themes and issues, including the legitimacy of military government, the tactical utility of genocide, and even the philosophical implications of artificial intelligence technologies for the very category of what it means to be 'human'. The contributors in this book explore in depth the argument that one of the most important aspects of popular culture is to naturalize or normalise a certain social order by further entrenching the expectations of social behaviour upon which our mentalities of rule are founded"--
Introduction: circulating on board the Battlestar -- Critical humanism: theory, methodology, and Battlestar Galactica -- Religion in sort of a global sense: the relevance of religious practices for political community in Battlestar Galactica and beyond -- Narrating identity, techno-rational subsumption and micropolitics in international relations and Battlestar Galactica -- Machines that matter: the politics and ethics of "unnatural" bodies -- Critical reflections on Battlestar Galactica and the hyperreal genocide -- So say who all? cosmopolitanism, hybridity, and colonialism in the re-imagined Battlestar Galactica -- Security or human security? civil-military relations in Battlestar Galactica -- Cylons in Baghdad: experiencing counter-insurgency in Battlestar Galactica -- Seeing others: Battlestar Galactica's portrayal of insurgents at a time of war -- Conclusion.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Battlestar Galactica (Television program : 2004-2009); Television programs -- Political aspects; Electronic books